GlyT1 determines the glycinergic phenotype of amacrine cells in the mouse retina - Eulenburg, Volker; Knop, Gabriel; Sedmak, Tina; Schuster, Stefanie; Hauf, Katharina; Schneider, Julia; Feigenspan, Andreas; Joachimsthaler, Anneka; Brandstätter, Johann Helmut (Brain Structure & Function, 2018)
The amino acid glycine acts as a neurotransmitter at both inhibitory glycinergic and excitatory glutamatergic synapses predominantly in caudal regions of the central nervous system but also in frontal brain regions and the retina. After its presynaptic release and binding to postsynaptic receptors at caudal glycinergic synapses, two high-affinity glycine transporters GlyT1 and GlyT2 remove glycine from the extracellular space. Glycinergic neurons express GlyT2, which is essential for the presynaptic replenishment of the transmitter, while glial-expressed GlyT1 was shown to control the extracellular glycine concentration. Here we show that GlyT1 expressed by glycinergic amacrine cells of the retina does not only contribute to the control of the extracellular glycine concentration in the retina but is also essential for the maintenance of the glycinergic transmitter phenotype of this cell population. Specifically, loss of GlyT1 from the glycinergic AII amacrine cells impairs AII-mediated glycinergic neurotransmission and alters regulation of the extracellular glycine concentration, without changes in the overall distribution and/or size of glycinergic synapses. Taken together, our results suggest that GlyT1 expressed by amacrine cells in the retina combines functions covered by neuronal GlyT2 and glial GlyT1 at caudal glycinergic synapses.
EVALuna2:35241

Inactivation of the Mouse L-Proline Transporter PROT Alters Glutamatergic Synapse Biochemistry and Perturbs Behaviors Required to Respond to Environmental Changes - Schulz, Daniel; Morschel, Julia; Schuster, Stefanie; Eulenburg, Volker; Gomeza, Jesus (Frontiers in Molecular Neuroscience, 2018)
The endogenous neutral amino acid L-proline exhibits a variety of physiological and behavioral actions in the nervous system, highlighting the importance of accurately regulating its extracellular abundance. The L-proline transporter PROT (Slc6A7) is believed to control the spatial and temporal distribution of L-proline at glutamatergic synapses by rapid uptake of this amino acid into presynaptic terminals. Despite the importance of members of the Slc6 transporter family regulating neurotransmitter signaling and homeostasis in brain, evidence that PROT dysfunction supports risk for mental illness is lacking. Here we report the disruption of the PROT gene by homologous recombination. Mice defective in PROT displayed altered expression of glutamate transmission-related synaptic proteins in cortex and thalamus. PROT deficiency perturbed mouse behavior, such as reduced locomotor activity, decreased approach motivation and impaired memory extinction. Thus, our study demonstrates that PROT regulates behaviors that are needed to respond to environmental changes in vivo and suggests that PROT dysfunctions might contribute to mental disorders showing altered response choice following task contingency changes.
EVALuna2:35242

Re-evaluation of neuronal P2X7 expression using novel mouse models and a P2X7-specific nanobody - Kaczmarek-Hajek, Karina; Zhang, Jiong; Kopp, Robin; Grosche, Antje; Rissiek, Bjoern; Saul, Anika; Bruzzone, Santina; Engel, Tobias; Jooss, Tina; Krautloher, Anna; Schuster, Stefanie; Magnus, Tim; et al. (eLife, 2018)
The P2X7 channel is involved in the pathogenesis of various CNS diseases. An increasing number of studies suggest its presence in neurons where its putative functions remain controversial for more than a decade. To resolve this issue and to provide a model for analysis of P2X7 functions, we generated P2X7 BAC transgenic mice that allow visualization of functional EGFP-tagged P2X7 receptors in vivo. Extensive characterization of these mice revealed dominant P2X7-EGFP protein expression in microglia, Bergmann glia, and oligodendrocytes, but not in neurons. These findings were further validated by microglia- and oligodendrocyte-specific P2X7 deletion and a novel P2X7-specific nanobody. In addition to the first quantitative analysis of P2X7 protein expression in the CNS, we show potential consequences of its overexpression in ischemic retina and post-traumatic cerebral cortex grey matter. This novel mouse model overcomes previous limitations in P2X7 research and will help to determine its physiological roles and contribution to diseases.
EVALuna2:35806